Volume 1: Development and Characterization of Multifunctional Materials; Modeling, Simulation and Control of Adaptive Systems; 2013
DOI: 10.1115/smasis2013-3258
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Control of Lozenge-Shaped Dielectric Elastomer Generators

Abstract: Dielectric Elastomers (DEs) are a very promising technology for the development of energy harvesting devices based on the variable-capacitance electrostatic generator principle. As compared to other technologies, DE Generators (DEGs) are solid-state energy conversion systems which potentially feature: 1) large energy densities, 2) good energy conversion efficiency that is rather independent of cycle frequency, 3) easiness of manufacturing and assembling, 4) high shock resistance, 5) silent operation, 6) low co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Initially proposed as muscle-like actuators for robots, DEs are now receiving significant attention in energy scavenging applications [2][3][4][5][6], in particular for the development of Wave Energy Converters (WECs) [7][8][9][10][11]. Specifically, DE Generators (DEGs) are foreseen to replace the Power-Take-Off (PTO) systems of traditional WECs, which are currently made of stiff, heavy, shock-sensitive, corrosion-sensitive and costly (metallic and rare-earth) materials.…”
Section: Introductionmentioning
confidence: 99%
“…Initially proposed as muscle-like actuators for robots, DEs are now receiving significant attention in energy scavenging applications [2][3][4][5][6], in particular for the development of Wave Energy Converters (WECs) [7][8][9][10][11]. Specifically, DE Generators (DEGs) are foreseen to replace the Power-Take-Off (PTO) systems of traditional WECs, which are currently made of stiff, heavy, shock-sensitive, corrosion-sensitive and costly (metallic and rare-earth) materials.…”
Section: Introductionmentioning
confidence: 99%
“…The relative permittivity of mix - co -P was 3.83 at 20 Hz. After the polar group modification, the dielectric permittivity increased to 5.23, which is higher than the VHB of 4.45–4.48 (1–10 Hz). Besides, tan δ (ε″/ε′ ratio) revealed that our materials can be operated at frequencies above 1 Hz where tan δ remains lower than 0.1. Additionally, the conductivity of all materials was below 10 –12 S/cm, which is rather low and further confirms the good dielectric properties of our materials.…”
Section: Resultsmentioning
confidence: 82%
“…Oscillating Bodies. The surge converter [117] has seen alternative forms with DEG implementation suggested by SBM [118] and Moretti et al [119,120], replacing the hydraulic pump PTO. In [118], the energy from flap movement is harvested by a vertical stack of DEG films.…”
Section: Implementation Into Wec Architecturesmentioning
confidence: 99%